Answer:
12
Step-by-step explanation:
Average of A and B is 6
(A+B) /2 = 6
Multiply each side by 2
A+B = 12
average of X, Y, and Z is 16
(X+Y+Z)/3 = 16
Multiply each side by 3
(X+Y+Z) = 48
To find the average of all of them
(A+B+X+Y+Z)/5
replace A+B with 12 and X+Y+Z with 48
(12+48)/5
60/5 = 12
Answer:
x = 0.1, y = 0.075
Step-by-step explanation:
Given the 2 equations
27x + 24y = 4.5 → (1)
1.5x + y = 0.225 → (2)
Multiplying (2) by - 24 and adding to (1) will eliminate the y- term
- 36x - 24y = - 5.4 → (3)
Add (1) and (3) term by term to eliminate y
- 9x = - 0.9 ( divide both sides by - 9 )
x = 0.1
Substitute x = 0.1 into either of the 2 equations and solve for y
Substituting into (2)
1.5(0.1) + y = 0.225
0.15 + y = 0.225 ( subtract 0.15 from both sides )
y = 0.075
Answer:
It's correct!
Step-by-step explanation:
Answer: A variable
Step-by-step explanation: